Social Audits in Nepal's Community Schools : Measuring Policy Against Practice - Prasad Kafle, Agni; Patel, Darshana; Agarwal, Sanjay (World Bank, Washington, DC, 2014)
Nepal s publicly-funded schools have been managed by community-level stakeholders since 1950 when Nepal first adopted a demo¬cratic system of government. Subsequent changes to legislation and policy have further devolved school management to the com¬munity level, including the provision of financial resources to support decision making by school-level committees. In addition to these reforms, each community school is now required to conduct an annual social audit. Community School National Network (CSNN), a national Nepali NGO with expertise in social accountability approaches, conducted a pilot of 60 schools in three districts (Kaski, Dolakha, and Nawalparasi) to assess gaps in the implementation of social audits by schools as specified in the Guidelines for the Social Auditing of the Schools issued by the Ministry of Education (MoE) of the Government of Nepal. In each of the three districts studied, 70 80 percent of the entire school budget is community-funded. Approximately 83 percent of community schools conducted social audits in the academic year 2008 09. Their implementation varied between the three districts but gaps were usu¬ally due to poor capacity and lack of information about community-level responsibilities. CSNN led a capacity-building initiative at the national, district, and community levels that included a training program for master trainers and facilitators who, in turn, strength-ened the capacity of the social audit committees (SACs) to collect data at the school level. CSNN also developed two templates to simplify data collection and monitor social audit implementation. The findings of this gap analysis and training program were disseminated through one national-level and three district-level workshops with the objective of influencing policy. A subsequent assessment of 20 schools in one of the pilot districts revealed that one iteration of the training effort has significantly improved community-level capacity to monitor and improve 22 of the 39 indicators in the Guidelines.